Demonstrating a High‐Resolution Gulf of Alaska Ocean Circulation Model Forced Across the Coastal Interface by High‐Resolution Terrestrial Hydrological Models. Issue 8 (21st August 2020) - Danielson, Seth L.; Hill, David F.; Hedstrom, Katherine S.; Beamer, Jordan; Curchitser, Enrique
Abstract: We demonstrate a linking of moderately high resolution (1 km) terrestrial hydrological models to a 3‐D ocean circulation model having similar resolution in the northern Gulf of Alaska, where a distributed line source of freshwater runoff exerts strong influence over the shelf's hydrographic structure and flow dynamics. The model interfacing is accomplished via mass flux boundary conditions through the ocean model coastal wall at all land‐ocean adjoining grid cells. Despite the high runoff volume and lack of a coastal mixing estuary, the implementation maintains numerical stability by prescribing depth invariant and surface‐intensified inflows at fast and slow discharge grid cells, respectively. Based on comparisons against in situ hydrographic data, the coastal sidewall mass flux boundary condition results in more realistic hindcast surface salinity and salinity gradient fields than models that distribute coastal runoff in the form of spatially distributed precipitation. Correlations with observed thermal and haline monthly anomalies reveal statistically significant hindcast temporal variability during the freshet season when the signal‐to‐noise ratio is large. Comparisons of ocean models forced by high‐ and low‐resolution hydrological models reveal differences in salinity, surface elevation, and velocity fields, highlighting the value and importance of accurate coastal runoff fields. The model results improve our understanding of the regional influence of runoff on sea level elevations and the distribution and fate of fresh water. Our approach has potential applications to biogeochemical modeling in regions where distributed line source freshwater coastal discharges deliver heat, momentum, and chemical constituents that may influence the marine carbon pump. Plain Language Summary: Fresh precipitation and snow melt runoff from the land enters the salty waters of the Gulf of Alaska, where it plays important roles in determining oceanic temperature and salinity distributions. Salinity distributions influence marine biological productivity, including that of economically important fisheries. Earth system hindcast models help us understand past conditions at times and locations that lack field observations. Models have struggled with generating accurate reproductions of the salinity field in the coastal Gulf of Alaska in part because coastal runoff directly enters relatively deep shelf waters (where mixing is relatively weak) and in part because of insufficiently accurate representations of coastal runoff. In this study we document an improved hindcast, whose results rely on both more accurate depictions of the runoff and the manner of incorporating this runoff into the ocean model. Our approach is compared to model results using more common configurations. This study improves our understanding of the fate of coastal runoff in the northern Gulf of Alaska. Key Points: High‐resolution terrestrial hydrological and ocean models are coupled with mass flux exchanges through the adjoining coastal interface The approach realizes improved hindcasts of marine freshwater distributions and pathways Regionally tuned hydrological models provide more locally accurate estimates of terrestrial runoff than global data sets